A parametric study of insertion and retention forces in cantilever hook - Siti Sarah, Abdul Manan; Muhammed Nafis, Osman Zahid (Faculty Mechanical Engineering, UMP, 2023)
Adhesive bonding, mechanical fastening, and snap-fit are all ways for attaching plastic components together. Snap-fit is employed to assemble plastic parts because it is an efficient, cost-effective, and fast joining technique. When it comes to snap-fits, you have two options: separable and inseparable. The term separable refers to the ability of the components to be dismantled successfully without breaking, whereas inseparable refers to the plastic parts being permanently attached. This investigation focuses on cantilever snap-fit since it is frequently used in the automotive, aerospace, and other sectors. Numerous aspects and parameters affect the functioning of snap-fits, notably on the forces of the insertion and retention. The parameters are the feature thickness (Tb), beam length (Lb), beam width (Wb), base radius (Rb), mounting (α) and dismounting angle (β). The forces required to attach and detach the snap-fits are thought to increase as the insertion and retention angles increase. The results can be seen that higher insertion and retention angle contributes to higher insertion and retention forces as portrayed from Set 7 with the value of 1.1052 N and -1.0214 N.